4(n+6)=2n-9

Simple and best practice solution for 4(n+6)=2n-9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(n+6)=2n-9 equation:


Simplifying
4(n + 6) = 2n + -9

Reorder the terms:
4(6 + n) = 2n + -9
(6 * 4 + n * 4) = 2n + -9
(24 + 4n) = 2n + -9

Reorder the terms:
24 + 4n = -9 + 2n

Solving
24 + 4n = -9 + 2n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-2n' to each side of the equation.
24 + 4n + -2n = -9 + 2n + -2n

Combine like terms: 4n + -2n = 2n
24 + 2n = -9 + 2n + -2n

Combine like terms: 2n + -2n = 0
24 + 2n = -9 + 0
24 + 2n = -9

Add '-24' to each side of the equation.
24 + -24 + 2n = -9 + -24

Combine like terms: 24 + -24 = 0
0 + 2n = -9 + -24
2n = -9 + -24

Combine like terms: -9 + -24 = -33
2n = -33

Divide each side by '2'.
n = -16.5

Simplifying
n = -16.5

See similar equations:

| 5h+17=2h+39 | | Y=4x-16x+33 | | 3.9(0.9x+7.34)=3.78x | | -6(x-1)17=-7x+2 | | 1/10(x-11)=-2(8-x) | | 10s+4n=84 | | 14x+25=73-2x | | (15/100)*x=50 | | 8x-2=12x-30 | | x^2+y^3-z^4=0 | | 9z+10=1-3(5-3) | | 1s=5s | | 3squared-(-5)= | | 9c=7c+8 | | 9x^2+4=(-12x) | | 15x-5+x=-47 | | 40=-10(1+a) | | 16+2(x+11)=36 | | (1/2^2x1/2x(1/2)^3= | | 15-4=3(5x-4) | | 18x+4y=162000 | | V=c-crt | | 15x+3=18x | | 3(2t+10)= | | 4*6+(6x)=150 | | log^4(9-4x)=1 | | -8x-(-3x+6)=4-x | | x+(1.10-x)=1.10 | | -44-7k=12-k | | C-11=19 | | X+2y=87.4 | | 5u-14=26 |

Equations solver categories